Uso de água da chuva e a incidência de diarreia em crianças - Araújo Junior, Pascoal do Sacramento (2016)
It is important to emphasize that both the quality of the water as the quantity and regularity of supply are determining factors for the emergence of diseases in humans. Therefore, we used the epidemiological ecological study, quantitative, in order to assess the consumption of rainwater and the incidence of diarrhea in children under 5 years of age: the exposed, which use capture systems roof rain water which is stored in tanks for potable purposes, composed of 111 children of the city of Lowland Roça-Ba; and not exposed, which use public water supply, composed also by 111 children of the city of Baixa Grande-Ba. Health indicators were adopted that diarrhea and measured over a period of 90 days. They were applied form, spreadsheet and field observation form with the families and children participating in the survey. The analysis of data obtained from said diarrhea and measured showed a significant association between episodes of diarrhea in the total sample of children studied and the spatial distribution where the highest concentrations occurred. Children who drank rain water had higher risk in percentage and time of occurrence, to have episodes of diarrhea than children who drink tap water, but with a difference not very acentuda. The incidence in children who consume rainwater stored in cisterns was 11.1%, and 5.8% in families who drink tap water.